Cooperative Carbon Alliances: Defining an Agenda for Global Industrial Decarbonisation - Aylin Shawkat; Oliver Sartor (Wirtschaftsdienst, 2022)
There have been several recent proposals for cooperative climate alliances, from the OECD, the IMF, the World Trade Organization (WTO), the German Government, and others. The "Climate Club" concept comprises many different possible regimes and intents. They range from so-called transformational clubs (which incentivise membership and penalise non-members), to looser joint agreements on ambition level for climate action, such as the UN's Net-Zero Coalition. Given this option, there is not yet any agreement on how to design such a "club", or its aims, rules, or scope of membership.
Keywords: O19; Q34; Q54; 330; Klimapolitik; Treibhausgas-Emissionen